2007
DOI: 10.1111/j.1472-765x.2007.02159.x
|View full text |Cite
|
Sign up to set email alerts
|

Enhanced activity of strobilurin and fludioxonil by using berberine and phenolic compounds to target fungal antioxidative stress response

Abstract: Aims:  Identify natural products that effectively target antioxidative signal transduction/stress response systems [i.e., mitogen‐activated protein kinase (MAPK) pathway, mitochondrial superoxide dismutase (Mn‐SOD)] of fungi. Enhance activity of strobilurin or fludioxonil with discovered compounds. Methods and Results:  Enhancement of antifungal activity of strobilurins, inhibitors of complex III of the mitochondrial respiratory chain, was tested using berberine hemisulfate and different phenolic compounds. Th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
24
0
4

Year Published

2011
2011
2023
2023

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 40 publications
(28 citation statements)
references
References 32 publications
0
24
0
4
Order By: Relevance
“…Such a strategy is called chemosensitization. One concept underlying the selection of putative chemosensitizers consists of increasing fungitoxic activity by disrupting fungal oxidative stress-response systems that protect the fungus from reactive oxygen species (ROS; Kim et al, 2006a, 2007, 2011). This approach has been demonstrated in vitro successfully by assays that include fungicides/antibiotics with compounds that disrupt the oxygen stress-response system, enhancing sensitivity of mycotoxigenic fungi and human pathogenic fungi of medical importance to antifungal agents (Kim et al, 2006b, 2008; Faria et al, 2011; Kim and Campbell, 2011).…”
Section: Discussionmentioning
confidence: 99%
“…Such a strategy is called chemosensitization. One concept underlying the selection of putative chemosensitizers consists of increasing fungitoxic activity by disrupting fungal oxidative stress-response systems that protect the fungus from reactive oxygen species (ROS; Kim et al, 2006a, 2007, 2011). This approach has been demonstrated in vitro successfully by assays that include fungicides/antibiotics with compounds that disrupt the oxygen stress-response system, enhancing sensitivity of mycotoxigenic fungi and human pathogenic fungi of medical importance to antifungal agents (Kim et al, 2006b, 2008; Faria et al, 2011; Kim and Campbell, 2011).…”
Section: Discussionmentioning
confidence: 99%
“…The initial discovery of natural products as chemosensitizing agents involved commercial agricultural fungicides (Kim et al. 2006, 2007, 2008b).…”
Section: Discussionmentioning
confidence: 99%
“…Additional natural compounds were also found to enhance activity of commercial fungicides. These included the alkaloid, berberine, and several phenolic compounds, enhancing antifungal activity of fludioxonil and strobilurin against A. flavus by further disrupting its oxidative stress response system (Kim et al, 2007a). Also tested were 2,3-dihydroxybenzaldehyde, salicylaldehyde and other benzo analogs.…”
Section: Chemosensitization Of Antifungal Agentsmentioning
confidence: 99%
“…The study showed that berberine disrupted Mn-SOD (mitochondrial superoxide dismutase) required for detoxification of ROS produced from the inhibition of mitochondrial respiration by strobilurin. Furthermore, this additional oxidative stress induced by berberine also resulted in overcoming resistance to fludioxonil (Kim et al, 2007a). …”
Section: Chemosensitization Of Antifungal Agentsmentioning
confidence: 99%